Website presentation for corporate social responsibility: The effect on corporate image - Mat Saat, Rafeah; Selamat, Mohamad Hisyam (2015)
Corporate Social Responsibility (CSR) becomes an important tool to create a constructive relationship between companies and consumers. The use of corporate website could build consumer acceptance towards the company.It is suggested for companies to enrich the CSR presentation by using media richness to increase consumers’ ability in analyzing and understanding the intended message. Thereafter, the consumers will have a positive attitude toward the company and at the same time increase the image of the company.This study aims to examine the role website presentation of CSR disclosure and its relationship with corporate image.This study utilizes laboratory experiment with two hundred forty one respondent that are divided into two different groups of presentation richness.Evidence was found that website presentation becomes one of the indicators in influencing consumer perception towards corporate image.The findings could be used to assist the companies in communicating CSR actions and portray a good image among the consumers.